Of People and Place: (Re-)Making Aotearoa - Matthew Wynyard (Landscape Review, 2022)
Review of Kia Whakanuia Te Whenua: People, Place, Landscape, Carolyn Hill (ed) for Landscape Foundation, Auckland: Mary Egan Publishing, ISBN: 9780473532376 (softcover).